Terrorism and counterterrorism studies: comparing theory and practice - Bakker, Edwin (Leiden University Press, 2015)
Terrorism has arguably been one of the defining factors of our age. In many parts of the world, it has in recent times been one of the most important threats to peace, security and stability. But what does this exactly mean? What is the nature of this threat? Who or what is threatened, how, by whom and why? What can be done about it or how can we at least limit the impact of terrorism and make sure that terrorists do not make headlines and manage to scare us? These are just a handful of questions that will be addressed in this handbook that consists of three parts. First it focuses on the essence of terrorism as an instrument to achieve certain goals. The second part provides an overview of the state of (counter) terrorism studies. Since 9/11 terrorism studies have grown exponentially, reflecting the rise in perceived threats. What theories, assumptions and conventional wisdom has it produced that could be of help in understanding terrorism and dealing with it? The final part looks into the implications and possibilities for policy making